Cameron: The first cut. Issue 2 (September 2014) - Seldon, Anthony
<x xml:space="preserve">Abstract</x> Exclusive to Juncture, political historian and biographer Anthony Seldon offers his first take on the Cameron premiership, and contends that the Conservative leader will be judged well when viewed against an unprecedented set of challenges and constraints.